A study of discovering dominant employer branding factor to increase employee engagement in generation y employees of xyz company - Antonia, Maria Rosana; Ginting, Henndy (Journal of Business and Management, 2020)
Abstract. Recruitment and Retention of employees is one of the concerns that need to be considered by the company because recruiting new employees requires a lot of costs, especially now when jobs began to be filled by generation Y employees. Generation Y employees have different characteristics compared to previous generation employees because they are more inclined to like to take risks and job-hopping. Therefore, to engage employees, an appropriate employer branding strategy is needed. This study aims to determine the dominant employer branding factor to increase employee engagement in XYZ companies. This research uses quantitative methods with Multilinear Regression to find out the most significant factor of employer branding. Data obtained by distributing questionnaires to XYZ company employees. The total of the respondent for this research is 135 employees. The results of this research found that significant factors were interesting work, job security, and appreciation & praise for work done. The most dominant employer branding factor in this research is Interesting Work. The recommendations given for XYZ companies are to give their employees challenging and interesting jobs, as well as provide opportunities for their employees to express their ideas.Keywords: Employer Branding, Employee Engagement, Generation Y